Effects of a severe drought on Quercus ilex radial growth and xylem anatomy (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.